Additive manufacturing of graded and anisotropic materials for applications at microwave frequencies - Wu, Y (2020)
Transformation optics (TO) allows the design of new optical devices for the novel manipulation of electromagnetic (EM) waves based on the spatial variation of relative permittivity and permeability, including at microwave frequencies. However, the practical manufacturing methods to realize these designs are limited. This thesis focuses on the investigation of additive manufacturing (AM) to the manufacture of devices that operate at microwave frequencies and involve spatial variations of dielectric permittivity within the device.